2012
DOI: 10.3109/s10165-011-0500-1
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept for the treatment of intractable hemophagocytic syndrome with systemic lupus erythematosus

Abstract: A 41-year-old woman presented with continuous fever, and her laboratory data suggested the recrudescence of systemic lupus erythematosus. She was treated with 60 mg/day prednisolone. With a dose reduction of prednisolone, high fever and pancytopenia were observed again. A bone marrow biopsy revealed hemophagocytosis. The effects of steroid pulse therapy, high-dose intravenous immunoglobulin, cyclosporine A, and methotrexate were insufficient. However, after four injections of etanercept (25 mg, twice a week) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It has been reported that anti-TNF therapy can significantly improve the severe respiratory syncytial virus and influenza in mice, thereby reducing the recruitment of inflammatory cells, disease duration, cytokine production induced by T cells, and the severity of illness (26). Blocking TNFα can strongly modulate the balance between effector T cells and regulatory T cells; as a result, approved TNF-α inhibitors play a crucial role in some severe autoimmune inflammatory diseases as well as numerous chronic inflammatory diseases such as psoriasis, rheumatoid arthritis (RA), inflammatory bowel disease (IBD) and ankylosing spondylitis, refractory hemophagocytic lymphohistiocytosis, systemic juvenile idiopathic arthritis, Behcet's disease, dermatomyositis, and lupus (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Although TNF coordinates the inflammatory response during the acute phase of inflammation, excessive TNF will suppress the immune system with the development of disease, which may lead to the adverse result (37).…”
Section: Tnf-α Signaling Pathway In Crsmentioning
confidence: 99%
“…It has been reported that anti-TNF therapy can significantly improve the severe respiratory syncytial virus and influenza in mice, thereby reducing the recruitment of inflammatory cells, disease duration, cytokine production induced by T cells, and the severity of illness (26). Blocking TNFα can strongly modulate the balance between effector T cells and regulatory T cells; as a result, approved TNF-α inhibitors play a crucial role in some severe autoimmune inflammatory diseases as well as numerous chronic inflammatory diseases such as psoriasis, rheumatoid arthritis (RA), inflammatory bowel disease (IBD) and ankylosing spondylitis, refractory hemophagocytic lymphohistiocytosis, systemic juvenile idiopathic arthritis, Behcet's disease, dermatomyositis, and lupus (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Although TNF coordinates the inflammatory response during the acute phase of inflammation, excessive TNF will suppress the immune system with the development of disease, which may lead to the adverse result (37).…”
Section: Tnf-α Signaling Pathway In Crsmentioning
confidence: 99%
“…Therefore, CsA was discontinued and he was treated with etanercept along with maintenance therapy that included etoposide, dexamethasone and vincristine. Etanercept can be used in therapy-resistant macrophage activation syndrome (MAS)/ HPS and several successful treatment cases were reported [14,15]. After the adoption of the etanercept, the ferritin levels were gradually decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous inflammatory cytokines including TNF-a are implicated in the pathophysiology of SLE [106,107]. Kikuchi et al [108] and Takahashi et al [109] successfully treated with etanercept 25 mg twice weekly 2 SLE women with intractable hemophagocytic syndrome. Although the risk of occurrence of anti-DNA antibodies seems to be more frequently in patients treated with infliximab [110], careful follow-up is required also in subjects receiving etanercept.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%